Data Quality of Travel Behavior Studies: Factors Influencing the Reporting Rate of Self-Reported and GPS-Recorded Trips in Persons with Disabilities. Issue 8 (December 2018) - Neven, An; Schutter, Ine De; Wets, Geert; Feys, Peter; Janssens, Davy
In persons with disabilities, the accuracy of self-report data collection methods in travel behavior studies may be influenced by disease-related dysfunctions. The present study determines in detail whether disease-related physical, cognitive or psychosocial impairments contribute to the reporting rate of subjective self-report travel diaries and objective GPS tracking devices, besides socio-demographic and trip-related characteristics. The reporting rate of both data collection methods was analyzed in 108 persons with Multiple Sclerosis with various disability severities during a seven-day data collection period. The results demonstrated that there was only limited influence of disease-related dysfunctions on the reporting rate of both data collection methods, as well as only limited significant differences between subgroups with various disability severity. Overall, the data quality of the diary was higher than the quality of the GPS data: 66% of the trips were reported in both data collection methods, while overall more than one fifth of all trips were forgotten and not registered by GPS, and 11% were forgotten and not reported in the diary. Self-report travel diaries seemed to be more suitable for persons with a higher disability severity, as these persons more often forgot to take their GPS device with them when making a trip because of several organizational issues related to their mobility limitations.